Preferred EFL Teaching Approaches to University Professors: A Case Study of Saudi Tertiary Level - AbdAlgane, Mohammed; Elmahdi, Omer Elsheikh Hago (International Journal of Language and Literary Studies, 2024)
This mixed methods study investigates Saudi university EFL professors’ perspectives on current teaching approaches and potential improvements needed. Surveys of 100 faculty and interviews with 10 department heads reveal a continued reliance on grammar-translation and lecture-based methods, despite broader recognition of communicative techniques as more effective. Systemic constraints like standardized curricula, assessments, textbooks, resources, and policies restrict implementation of innovative practices. Though professors acknowledge challenges with prevailing methods, most believe they sufficiently improve English skills, indicating a disconnect between beliefs and second language acquisition theory. Strong support for training in modern approaches shows openness to change given adequate guidance. Recommendations include reforming teacher preparation, balancing grammar with communicative activities, allowing materials flexibility, and linking evaluations to student progress. Updating systemic constraints and empowering educators are critical to shift entrenched practices towards communication-focused instruction aligned with Saudi reform goals. The study provides insights into translating positive perspectives into transformative policies and teaching practices that enhance university student outcomes.